Écriture et trauma dans “The Giant Wistaria” : Quand Charlotte Perkins Gilman revisite le gothique - Paule Lévy (Sillages Critiques)
This article purports to highlight the relationship between text and trauma in Gilman’s, “The Giant Wistaria”, a short story based on one of the topoi of the gothic tradition: the haunted mansion.Gilman humorously introduces a “trouble in the genre”, turning her dark tale into a subversive version of the birth of the American nation. Espousing the very structure of trauma, the text oscillates between rupture and continuity, denial and reminiscence, growth and regression. Far from being seen as a radical uprooting from Europe and a miraculous renewal in the New World, the Founding of the Nation is depicted as a grotesque transplantation of patriarchal injustice and arbitrariness.This remarkably effective tale, may also be seen as a young writer’s attempt to carve out a “Room of [her] Own” within the American “House of Fiction”. It remains, however, relegated to the margins of literary production and haunted by the overbearing shadows of her predecessors.